2016
DOI: 10.2169/internalmedicine.55.6793
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Closure of Duodenal Perforation with the Over-the-scope-clipping System

Abstract: Endoscopic treatment for superficial non-ampullary duodenal tumors is technically difficult and challenging due to the anatomical characteristics of the duodenum. It is frequently complicated by procedural accidents, such as perforation. Surgical repair has long been the standard treatment for acute iatrogenic gastrointestinal perforation. However, endoscopic closure has recently emerged as an attractive alternative. In the patient presented herein, the over-the-scope-clipping system (OTSC system) was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…11 However, ESD as an increased complication rate, and is technically challenging, even in expert hand, due to anatomical duodenal specificitiesthinner duodenal muscular wall, location in retroperitoneum, narrow lumen, rich submucosal vasculature, abundant Brunner's glands that inhibit proper mucosal lifting and submucosal fibrosis and technical difficulties. 3,5,6,8,14 Thermal injury or repeated coagulation, causing ischemic changes in duodenum wall, are also associated. 4,6 Perforation and bleeding are two potential dangerous complications of ESD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 However, ESD as an increased complication rate, and is technically challenging, even in expert hand, due to anatomical duodenal specificitiesthinner duodenal muscular wall, location in retroperitoneum, narrow lumen, rich submucosal vasculature, abundant Brunner's glands that inhibit proper mucosal lifting and submucosal fibrosis and technical difficulties. 3,5,6,8,14 Thermal injury or repeated coagulation, causing ischemic changes in duodenum wall, are also associated. 4,6 Perforation and bleeding are two potential dangerous complications of ESD.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has a success rate until 87.8%. 5 Completely closing could be difficult, especially in the distal portion of duodenum but, in order to improve outcomes, it is necessary complete closure of the whole mucosal defect. 6,18 Some studies show using those clips to perform prophylactic clipping after endoscopic resection, although some authors don't agree that is sufficient to prevent delayed perforation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of reports have demonstrated the successful prophylactic closure of post-duodenal ESD using OTSC, there are few reports on the complete closure of perforation during ESD. In the current issue of this journal, Furukawa et al reported, for the first time, a case in which with closure and hemostasis were simultaneously achieved in a patient with arterial bleeding during duodenal ESD using the OTSC system ( 4 ).…”
mentioning
confidence: 99%